Water quality assessment in Benue South, Nigeria: An investigation of physico-chemical and microbial characteristics - Augustine O. Edegbene; Doowuese Yandev; Temidayo O. Omotehinwa; Hajara Zakari; Blessing O. Andy (Water Science)
A high proportion of chemical substances and microorganisms in water can result in water-borne diseases which can be harmful to humans when such water is consumed untreated. We used physico-chemical and microbial characteristics to assessed the water quality of selected water sources in Benue South, Nigeria. Three Local Government Areas namely, Otukpo, Ohimini, and Apa were studied. This study combined field and laboratory-based approach where water samples were collected from particular water sources within the study area from January 2023, March–May 2023 (four months). Temperature, pH, TDS, and EC were measured insitu while TSS, COD, DO, BOD, and turbidity were determined in the laboratory following standard procedures, and microbial analysis was estimated based on standard microbiological procedures. Data obtained were analyzed using descriptive statistics (mean± S.D), two-way ANOVA, and Post Hoc test and Principal Component Analysis (PCA) was used to check the association between physico-chemical variables of the sites sampled in the study area. The results of the physico-chemical variables showed markedly high values of EC, BOD, COD, TDS, TSS, and turbidity with no significant difference (p > 0.05) in physico-chemical values across themonths. Water temperature, DO, EC, and TDS were positively associated with S5 in the first component of the PCA while COD and pH were slightly negatively associated with S2 in the first component of the PCA. Microorganisms detected were Klebsiella sp., Proteus sp., Shigella sp., Bacillus sp., Escherichia coli and Staphyloccus sp. The highest coliform count was recorded in S1: January: >1,600 MPN/100 mL: March (>1400MPN/100 mL), April 2023: (>1300MPN/100 mL) and May: (>950MPN/100 mL). Total viable count (TVC; 136 ± 39.10) and (TCC); 90.75 ± 27.80) were highest in S5 across the months. The post hoc test showed that TCC and TVC were not significantly different among sites (p > 0.05). Elevated total coliform counts were recorded in the sites above the recommended limit by the World Health Organization standard (3 coliform/100 mL). Therefore, there is the need for regulatory action to address water quality issues within the study area.